Analisis Efektivitas, Efisiensi, dan Kebijakan Pembiayaan di TK ABC: Studi Kasus Pengelolaan Keuangan Pendidikan Anak Usia Dini - Sopi Ali; Tanti Harjanti; Suprobo Pulas Dewi; Rusmiyanti Rusmiyanti; Sisca Septiani; Wiwik Pudjaningsih; Idah Riyanti (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study aims to analyze the effectiveness, efficiency, and financing policies in ABC Kindergarten, considering the importance of optimal financial management in ensuring the quality of educational services and the sustainability of the institution. Financing issues are often a major challenge in early childhood education, especially related to limited funds, increasing operational needs, and demands for transparency and accountability. Therefore, a comprehensive evaluation is necessary to find a strategy for improvement. The research method uses a descriptive qualitative approach with case studies. Data was collected through in-depth interviews with principals, treasurers, teachers, and school committees; direct observation in the school environment; and analysis of financial documents and annual budgets. The analysis was carried out thematically to identify financing management patterns, the effectiveness of the use of funds, and the challenges faced. The results of the study show that the effectiveness of financing in supporting the learning process and the provision of basic facilities is quite good, although there is room for optimization, especially in supporting facilities. From an efficiency perspective, the use of funds is relatively economical, but the recording and reporting system is not fully automated, so it has the potential to cause delays in financial information. Meanwhile, financing policies based on parental contributions and foundation subsidies have proven to help maintain operational sustainability, but are still limited in terms of diversifying funding sources. This study recommends the need to improve a digital-based accounting system to strengthen transparency, increase the managerial capacity of school treasurers, as well as efforts to find alternative sources of financing such as cooperation with the private sector, the business world, or government programs. In addition, broader community involvement and strengthening internal governance are also important to ensure sustainable and accountable financing management for all stakeholders.